Effectiveness Factors of Interactive Training in Teaching Preschool Logopedics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the factors of the effectiveness of interactive training in teaching the science of speech therapy before school, the main criteria of interactive education: conducting informal discussions, the opportunity to freely describe and express the educational material, small group, large group, class team Opinions about giving assignments, doing written work and using other methods for working with lib are expressed.